2019
DOI: 10.3329/ralf.v6i1.41381
|View full text |Cite
|
Sign up to set email alerts
|

Organic amendments for mitigating soil salinity in rice

Abstract: Salinity causes cellular damage and limits crop productivity. Accumulation of organic compound is one of the adaptive mechanisms to salinity in plants. The experiments were laid out in a randomized complete block design with three replications at the farmer’s field of Botiaghata, Khulna to investigate the mitigating effects of organic manures on salinity stress in rice genotypes during both aman and boro seasons. Two T. aman rice (salt-sensitive; BR-23 and local cultivar; Mohini) and two boro rice (salt-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…Na + /K + is considered a good index for assessing the damages of SS. We noted that SS increased Na + /K + which is consistent with the results of Xu et al [79] and Khan et al [19]; they also observed a significant increase in Na + /K + under SS. However, OA caused a reduction in the Na + /K + ratio, which indicates OA amendments decrease Na + accumulation and increase K + uptake, which maintains a lower Na + /K + ratio [80,81].…”
Section: Discussionsupporting
confidence: 92%
“…Na + /K + is considered a good index for assessing the damages of SS. We noted that SS increased Na + /K + which is consistent with the results of Xu et al [79] and Khan et al [19]; they also observed a significant increase in Na + /K + under SS. However, OA caused a reduction in the Na + /K + ratio, which indicates OA amendments decrease Na + accumulation and increase K + uptake, which maintains a lower Na + /K + ratio [80,81].…”
Section: Discussionsupporting
confidence: 92%
“…Variation in number of panicle m -2 , grains panicle -1 and individual grain weight in different rice varieties in saline soils was also reported by Joseph and Mohanan (2013). Chowdhury et al (2019) found soil amendments with FYM and poultry manure significantly increased the growth, and grain and straw yields of all rice cultivars under saline conditions. In 2019-20, grain yield (6.63 t ha -1 ) were highest in land ploughed at 20 cm depth by 5 times.…”
Section: Chemical Analysis Of Soil Samplesupporting
confidence: 53%
“…Biochar has the ability to reduce toxic elements by the process of adsorption [62]. Salt-affected soil amended with farmyard and poultry manures for rice showed enhanced growth and yield, increased amounts of potassium and K/Na, and increased salt-tolerance [63].…”
Section: Post-harvest Soil Characteristicsmentioning
confidence: 99%